Direct simulation of viscous flow in a wavy pipe using the lattice Boltzmann approach. (20th June 2008) - Wang, Lian-Ping; Du, Michael H.
Direct numerical simulation of three-dimensional (3D) viscous flow in a wavy pipe is performed using the lattice Boltzmann approach, to study 3D flow features in a curved pipe with nonuniform curvature. We first validate the lattice Boltzmann approach by simulating a transient flow in a straight pipe. In a wavy pipe, it is shown that the pressure gradient necessary to drive the flow depends more strongly on the flow Reynolds number, due to curvature ? induced fluid inertial force and transverse secondary flows. The wavy pipe could provide a simple design for enhancing mixing and heat transfer in pipes.